Thermally assisted alkali/zinc ion hybrid battery for high roundtrip efficiency - Liu, Yezhou (2022)
The growth of renewable energy generation has necessitated electric energy storage (EES) systems. Batteries are the most promising small-scale EES system, given their portability, quick response time, and high compatibility with electrical devices. We present a thermally assisted K/Zn ion hybrid battery for high roundtrip efficiency. The battery contains a copper hexacyanoferrate (CuHCFe) cathode and a zinc metal anode with a discharging voltage of 1.75 V in a K/Zn ion hybrid aqueous electrolyte. The battery's roundtrip efficiency improved by 2.1-4.5% when cycled between 10 and 30 °C. Its discharging voltage and temperature coefficient improved dramatically when the K ion was replaced with a Rb ion. The proposed thermally assisted battery cycle can be used with various conventional batteries to reduce EES energy loss during charge/discharge cycles.